Alpha tocopherol-Nanocellulose loaded alginate membranes and Pluronic hydrogels for diabetic wound healing - Anha Afrin Shefa; Myeongki Park; Jae-Gyoung Gwon; Byong-Taek Lee (Materials & Design, 2022)
Due to the non-healing nature of chronic diabetic wounds, a novel wound healing agent is required to provide the nutrients to wound and cover the wound surfaces. In this study, Alginate (ALG) membrane and Pluronic® F-127(P) hydrogel incorporated with alpha-tocopherol (AT) and TEMPO-oxidized cellulose nanofibers (TOCN) were designed. The ALG-TOCN-AT membrane was prepared using the casting method and P-TOCN-AT thermos-sensitive hydrogel was prepared using the cold mixing method. The gelation time of the P-TOCN-AT hydrogel was 45 ± 1.2 s at 37 °C and the viscosity of the hydrogel at 37 °C was higher than the viscosity measured at 25 °C. Further, the addition of TOCN and AT significantly improved the tensile strain of the membrane. An immediate release of AT was achieved in P-TOCN-AT gel while the ALG-TOCN-AT membrane released AT in a sustained manner. Cell proliferation study revealed the nontoxic nature of the hydrogel and membrane. Full-thickness skin wounds of diabetic rats were better healed by combined use of membrane and hydrogel compared to individual application of membrane or hydrogel. The highest neoepithelialization and angiogenesis was confirmed through CD31, CD105, and CD34 gene expression analysis. Hence, the combined application of hydrogels and membranes showed enhanced angiogenesis along with accelerated wound healing with no observable in-vivo toxicity.